Bilateral Giant Juvenile Fibroadenoma of Breast - Makkar, Nikhil (J Clin Diagn Res, 2017)
Fibroadenomas are benign lesions of breast commonly found in young age group. These focal tumours contain both mesenchymal and glandular tissue. Giant juvenile fibroma of breast is rare variant of fibroadenoma found usually in less than 20 years of age. They present with rapid enlargement of single or multiple, discrete, painless large nodule of breast. A 14-years-old premenarche girl presented with large bilateral breast lumps for two months. FNAC showed features of juvenile fibroadenoma. Breast conserving surgical excision of lumps was performed and histopathology confirmed the diagnosis of juvenile fibroadenoma. Giant juvenile fibroadenomas are characterised by rapid enlargement of encapsulated mass. The aetiology is unknown, although end-organ hypersensitivity to normal level of estrogen is postulated. We present a case of bilateral giant juvenile fibroadenoma for its rarity.